Africa’s Growing Soil Fertility Crisis : What Role For Fertilizer? - Agwe, Jonathan; Morris, Michael; Fernabdes, Erick (2012)
Reversing Africa's decades-long decline in soil productivity levels poses a major challenge, and one that cannot be addressed without increased use of appropriate fertilizer nutrients. The 2006 World Bank Africa Fertilizer Strategy Assessment was undertaken to inform policy makers, providing them with guidelines on measures to effectively raise fertilizer use. This Note draws upon the material prepared for the above fertilizer strategy assessment, summarizes the information on the approaches to enhancing fertilizer supply and use in Africa, and identifies some future steps.